(untitled) (Polis (Santiago), 2023)
Through documentary and bibliographical research understanding that Brazil is experiencing a scenario of hyperincarceration, we propose with this text a systematization about the numbers of deaths caused by the Coronavirus Pandemic (Covid-19) between 2020-2022 and its underreporting in the Brazilian penitentiary system, in order to demonstrate in an organized way the total numbers of lives lost and resistance initiatives that have erupted during this pandemic time. Concluding that the inertia of the state is part of a state project of genocide of the black and peripheral population that intersects with gender inequalities, a clientele almost exclusive to the Brazilian prison.